2014
DOI: 10.1002/2013ja019471
|View full text |Cite
|
Sign up to set email alerts
|

Size and shape of the distant magnetotail

Abstract: We employ a global magnetohydrodynamic model to study the effects of the interplanetary magnetic field (IMF) strength and direction upon the cross section of the magnetotail at lunar distances. The anisotropic pressure of draped magnetosheath magnetic field lines and the inclusion of a reconnection-generated standing slow mode wave fan bounded by a rotational discontinuity within the definition of the magnetotail result in cross sections elongated in the direction parallel to the component of the IMF in the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 51 publications
7
35
0
2
Order By: Relevance
“…Observations discussed by Lavraud et al [] confirmed this and also showed that this asymmetry is more pronounced in the case of low Mach numbers. Similar conclusions were also reached by Sibeck and Lin [] in their modeling study.…”
Section: Introductionsupporting
confidence: 90%
“…Observations discussed by Lavraud et al [] confirmed this and also showed that this asymmetry is more pronounced in the case of low Mach numbers. Similar conclusions were also reached by Sibeck and Lin [] in their modeling study.…”
Section: Introductionsupporting
confidence: 90%
“…For example, bow shock reflection should create hot electrons predominantly in the duskside magnetosheath [ Sibeck and McEntire , ]. The locations of the magnetopause reconnection in the tail have a dawn‐dusk asymmetry depending on the IMF B y direction [ Sibeck and Lin , ]. The magnetosphere electrons may be hotter on the dawnside due to drift effect, thus may result in stronger enhancements in the dawnside magnetosheath [e.g., Imada et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…A Figura 1 apresenta as regiões mais importantes que compõem a magnetosfera terrestre [2,9,10]. O lado diurno, queé a região voltada para o Sol no lado esquerdo da Figura 1, estende-se, tipicamente, por 10 raios terrestres 3 em condições de vento solar calmo.…”
Section: A Interação Vento Solarmagnetosfera Terrestreunclassified
“…A magnetocauda pode chegar a distâncias superiores a 200 raios terrestres, sendo considerado um grande reservatório de energia e plasma [2,9,10].…”
Section: A Interação Vento Solarmagnetosfera Terrestreunclassified